Two Daily Subcutaneous Injections of Fragmin as Compared with Intravenous Standard Heparin in the Treatment of Deep Venous Thrombosis (DVT) - Bratt, Göran; Åberg, Wiveca; Johansson, Margareta; Törnebohm, Eva; Granqvist, Staffan; Lockner, Dieter (Thrombosis and Haemostasis, 1990)
In a prospective, randomized, open study 119 consecutive patients with phlebographically verified deep venous thrombosis (DVT) of the leg (36% distal and 64% proximal) were treated either with a low molecular weight heparin (Fragmin, Kabi-Vitrum) subcutaneously (120 anti-FXa U/kg) twice daily or standard heparin (SH) as continuous intravenous infusion (480 IU kg−1 day−1). The Fragmin doses were adjusted to achieve an anti-FXa activity of 0.2-0.4 U/ml before injection and not greater than 1.5 U/ml 4 h after the morning injection. The SH dose was modified to prolong the APTT 2-3 times.Repeat phlebography after 5-7 days showed improvement in 34/45 patients (76%) in the Fragmin group and in 30/49 patients (61%) in the SH group and progress in 2/45 (4%) and 3/49 (6%), respectively. The mean Marder scores decreased from 18.7 ± 12.1 to 15.7 ± 12.7 in the Fragmin group and from 16.9 ± 12.0 to 14.4 ± 11.8 in the SH group (ns). Two patients in the SH group and none in the Fragmin group had major bleedings.After 22 ± 7 months follow up 6 rethromboses had occurred in the SH group and 4 in the Fragmin group. Postthrombotic signs and symptoms were similar in both groups.We conclude that two daily sc Fragmin doses seem as effective and safe as continuous SH in the treatment of DVT of the leg.